Editorial Thematic Section: Science, Technology & Society Studies, Psy Practices and different ways of subjectivity production - Vicente Sisto; Escuela de Psicología, Pontificia Universidad Católica de Valparaíso; Verónica López; Escuela de Psicología, Pontificia Universidad Católica de Valparaíso; Jorge Castillo-Sepúlveda; Universidad de Santiago de Chile; Arthur Arruda Leal Ferreira; Universidade Federal do Rio de Janeiro; Juan Felipe Espinosa-Cristia; Universidad Andrés Bello (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2017)
The Thematic Section that we publish in this issue seeks to open a space for the dissemination of research and theoretical reviews of what has been called "Psi Practices". In recent years, there has been a growing interest in questioning the descriptive potential of traditional perspectives, and even the so-called critical social approaches, regarding the composition of the subject and subjectivity in contemporaneity. Such questions are grouped into a series of derivative works in the field of Social Studies of Science and Technology, or studies of Science, Technology and Society (CTS), which address, among other aspects, the heterogeneous processes in which stable versions are produced about the reality, the facts, and the opening and closing of the discussions to the base. Regarding the studies on the subject, some approaches vindicate that the place of the human and the subjectivity can be recomposed if they are approached from the perspective of their association with entities of diverse nature. That is, consider the subject as an effect or product, rather than a starting point. In this way, it is possible to study the subjective formations as the association of efforts between humans and non-humans, reconfiguring in the process both the meaning and notion of the self, and the tools by which research is generated and developed.